Creating An Enabling Environment For A Successful Partnership In Housing Delivery. (A Case Study of Kaduna State, Nigeria). - Abeku, D. M.; Luka, C. K. (Advances in Social Sciences Research Journal, 2019)
The provision of affordable housing in Nigeria has remained a mirage in spite of the huge deficit which is put at seventeen (17) million units required to bridge the gap, unfortunately, government’s effort in terms of policy, funding, direct construction and mortgage provisions has yielded next to nothing over the years as the gap keeps widening. It is as a result of this that government introduced the public private partnership (PPP) arrangement to cater for infrastructural deficit, housing inclusive. The methodology include the inductive method where stakeholder organizations such as Kaduna Investment Promotion Agency (KADIPA), Kaduna Geographic Information Systems (KADGIS), Kaduna Urban Planning and Development Authority (KASUPDA), Kaduna Roads Agency (KADRA), Kaduna Power Supply Company (KAPSCO), Kaduna State Water Corporation (KADSWAC), Kaduna State Development and Property Company Limited (KSDPC) and Ministry of Works, Housing and Transport (MOWH&T) were visited to ascertain their involvement in the housing effort of the state. The researchers also visited five (5) housing development sites to confirm the information from the side of the government. Results showed that seventeen (17) developers have been engaged by the state government through the ppp arrangement within the last two (2) years with an approximate size of 185.8 hectares of land shared among the developers at various locations within the metropolis who are developing various types of houses. The challenge of affordability of the houses to the poor and low income earners still remains a major problem as the average price of one bedroom semi detach is between N3 million and N4 Million, while a two bedroom semi detach is put at N6 million and a three bedroom ranges between N7.5 million and N8 million. To the poor, these prices are extremely high and unattainable. Therefore, house ownership for this category remains a tall dream. The study recommends the construction of the single room (studio) apartments and the sourcing of cheaper building materials to construct these houses so that the poor and the low income earners can afford them.